Attitudes and beliefs people with head and neck cancer hold towards food and nutrition : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Nutrition and Dietetics, Massey University, Albany, New Zealand - Young, Ruby (Massey University, 2024)
Background: Head and neck cancers (HNC) are devastating diseases that have significant impacts on a person’s ability to achieve adequate nutrition. HNC treatments and subsequent side effects often cause nausea, taste changes, appetite loss, and most harmfully malnutrition. The severity of these side effects can leave people searching for ways to improve their condition and can lead to the development of strong attitudes and beliefs towards nutrition, some of which are evidence-based and others which are not. Dietary changes that are not evidence-based can lead to reduced recovery, and survival. Objectives: Explore the attitudes and beliefs people with HNC hold towards food and nutrition in HNC prevention, causation, treatment, and recovery. Methods: This study collected qualitative data using an online survey. Data was analysed manually using an inductive thematic analysis. All 39 participants were over 18 years of age, had been diagnosed with, and treated for, HNC in New Zealand (NZ), were currently living in NZ, and could independently complete the survey. Results: The themes were participants’ sources and perceptions of nutrition information, perceptions of food and nutrition, and participants’ desire for additional support. The information sources people with HNC accessed the most and held in the highest regard were dietitians and survivors of HNC due to their relatable support and focus on evidence-based information. Alcohol, energy and protein were correctly identified to have significant roles in HNC. Additionally, very few participants believed the alternative dietary therapies mentioned were effective (ketogenic diet, high-dose vitamin C, prioritisation of fruits and vegetables), further indicating that participants valued evidence-based information and support. Finally, participants desired support for unintentional weight loss, involvement in treatment decision-making, receptivity to their opinions, and advice regarding long term recovery recommendations. These findings highlighted the need for open communication between healthcare professionals and people with HNC. Conclusion: The nutrition beliefs identified in this study highlighted the quality and range of dietary support available to people with HNC in NZ. The findings of this study provided insight into the areas of nutrition education and support that require improvement to ensure that people with HNC achieve the best possible health outcomes.
Keywords: head and neck cancer; survey; nutrition; attitudes; beliefs; 321004 Nutritional science